The Influence of E-Commerce Technology Implementation on Business Development in the Digital Era - Marcello Pieterson Tulong; Reyk pangandaheng; Jesica Cristy Tataung; Natalia Caroline Gloria Manobi; Stevanus Marvi Singal Rumbajan; Luke Alfie Nongko (Jurnal Syntax Admiration, 2024)
E-commerce has become an integral part of modern business practices, driven by the increasing demand for convenience and efficiency in the digital era. As more people turn to online platforms for transactions, understanding the factors that influence e-commerce adoption and its impact on business growth has become crucial. This research aims to explore the role of e-commerce technology in business growth, identifying both the supporting factors and barriers that affect its implementation in the digital era. The study employs a mixed-method approach, combining qualitative and quantitative research methods. Data were collected using surveys from 200 small and medium-sized enterprises (SMEs) in the retail sector, alongside in-depth interviews with 15 business owners. The results indicate that e-commerce technology significantly enhances business growth by increasing market reach, improving operational efficiency, and providing customer insights. However, challenges such as technological infrastructure limitations, cybersecurity concerns, and resistance to change were identified as barriers to successful e-commerce adoption. This research concludes that while e-commerce plays a vital role in driving business growth, addressing these barriers is essential for businesses to fully leverage the benefits of digital commerce. The study contributes to understanding how businesses can overcome obstacles to e-commerce adoption and thrive in the digital economy.